Roles of the Wnt Signaling Pathway in Head and Neck Squamous Cell Carcinoma - Xie, Jing; Huang, Li; Lu, You-Guang; Zheng, Da-Li (Frontiers in Molecular Biosciences, 2021)
Head and neck squamous cell carcinoma (HNSCC) is the most common type of head and neck tumor. It is a high incidence malignant tumor associated with a low survival rate and limited treatment options. Accumulating conclusions indicate that the Wnt signaling pathway plays a vital role in the pathobiological process of HNSCC. The canonical Wnt/β-catenin signaling pathway affects a variety of cellular progression, enabling tumor cells to maintain and further promote the immature stem-like phenotype, proliferate, prolong survival, and gain invasiveness. Genomic studies of head and neck tumors have shown that although β-catenin is not frequently mutated in HNSCC, its activity is not inhibited by mutations in upstream gene encoding β-catenin, NOTCH1, FAT1, and AJUBA. Genetic defects affect the components of the Wnt pathway in oral squamous cell carcinoma (OSCC) and the epigenetic mechanisms that regulate inhibitors of the Wnt pathway. This paper aims to summarize the groundbreaking discoveries and recent advances involving the Wnt signaling pathway and highlight the relevance of this pathway in head and neck squamous cell cancer, which will help provide new insights into improving the treatment of human HNSCC by interfering with the transcriptional signaling of Wnt.